Socialização profissional dos professores engenheiros ingressantes na educação superior - Santos, Patricia Peixoto dos (2013)
The goal of this research was to investigate how the socialization process of the new-coming professors takes place in the Federal University of Uberlândia (Universidade Federal de Uberlândia), that is, in the engineering courses, mainly in thecivil, chemical,electrical, mechanical, and the mechatronic courses. The subjects of the investigation were the new-coming professors, who had more than three years of experience of teaching in the field. The data were built up by means of a questionnaire and an reflexive interview which made available the ideas of training, present in their teaching practice, as well as the main scientific concepts within the knowledge they judged to be relevant for the training of teachers in the university. So, we tried to check outthe concepts of teaching, knowledge and practice, professional identity, professional socialization, professional development, initial and continuing training, the relation between theory and practice, learning process, assessment, the training needs to be a teacher, the role ofdidactic and pedagogical knowledge in teaching. The question whichconducted this research was the following: How does the socialization process of the new-coming professors of Higher Education who work the courses of Engineeringin the Federal University of Uberlândiatake place? A meaningful part of the group of professors had their education in a continuous process which began in graduation and post-graduation programs (Master and Doctorate programs) and later joined the educational career. The reality presented teachers who had no teaching experience,whose main education was in research and little experience in teaching and small pedagogical support in the universities they had worked. Based on analysis of the data, we can state that they succeeded in the career by means of errors and trials as strategies of teaching. All engineer professors who took part in the research pointed out the importance of the continuous education and the role of the university, when it offers opportunities and support for the new teachers in the field of Engineering. In summary, this work points out the necessity of institutional policies of pedagogical formation and of the recognition of the values of teachers within the university. Such policies must offer well-structured programs which cover the professional development of teachers, and aim to improve the quality of the education offered to students of Higher Education.